KEWAJIBAN PENCANTUMAN PESAN KESEHATAN PADA MINUMAN KOPI KEMASAN DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN: The Obligation To Include Health Messages On Packaged Coffee Drink Labels From A Consumer Protection Perspective - Rosy Aisyah; Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2025)
Coffee beverages are among the processed foods favored by various groups. Pursuant to Minister of Health Regulation Number 30 of 2013, processed foods containing sugar, salt, and fat (GGL) are required to include health warnings on their packaging labels. Based on the research object, it was found that only 1 out of 25 coffee beverage products displayed a health warning on its label. This study identifies problems concerning the regulation of mandatory health warnings regarding sugar content on packaged coffee beverages and the supervisory function over the fulfillment of such obligations. The findings indicate that the enforcement of mandatory health warnings related to sugar content on packaged coffee beverages has mostly not been implemented by business actors. Among the 25 coffee beverage products studied, only one product displayed the required health warning, namely Del Monte Vanilla Latte. The supervisory function over the mandatory health warning labeling has been carried out by the authorities. However, this function remains general and has not yet specifically focused on the inclusion of health warnings on packaging labels. With the results of the research and conclusion, it was found that the implementation of mandatory health warning labeling remains weak, requiring more targeted supervision to ensure the regulation is effectively enforced.